Eyes On Bangladesh’s Disappearing Coasts: Proposed Constitutional Protections For Coastal Communities Particularly Vulnerable To Climate Change - Persaud, Sabrina (Journal of Sustainable Development Law and Policy, 2025)
Climate change, a phenomenon caused by global warming, has impacted just about every part of the earth. As polar ice caps continue to melt, people across the world are experiencing record-breaking heat waves and warmer winters. These erratic weather patterns are just one of the many impacts of climate change. Changes in temperature have altered ecosystems and habitats for terrestrial and marine wildlife, and caused human health to deteriorate. Larger, more industrialized countries are the major contributors to climate change; however, smaller countries, such as Bangladesh, suffer the consequences. This article analyses the negative effects that climate change has had on Bangladesh, particularly the vulnerable coastal communities of Bangladesh. Warmer temperatures lead to warmer waters, a breeding ground for tropical cyclones and spells disaster for those living along Bangladesh’s coasts. This article proceeds to suggest possible domestic and international legal solutions to the problem and examines the law that supports these proposals.